Impacts of Longitudinal Mentorship to Strengthen the HIV Workforce: Qualitative Evidence of Changes in Clinicians' Knowledge, Attitudes, and Practice. (November 2017) - Wagner, Cornelia M.J.; Carlberg‐Racich, Suzanne; Linsk, Nathan L.; Sherer, Renslow; Alabduljabbar, Salma A.; Hasnain, Memoona; Rivero, Ricardo
Abstract : N/A: The Clinician Scholars Program at the Midwest AIDS Training and Education Center strengthens the workforce by increasing knowledge and skills related to HIV prevention and care. The 1‐year individualized training program for minority‐serving clinicians includes intensive mentoring and networking. Qualitative exit interviews ( N = 50) conducted over 4 years demonstrate the effectiveness of the training, including changes at the individual and systems levels. Findings show that almost all graduates reported improvements in knowledge, two‐thirds reported changes in empathic capacity and cultural competence, and nearly three‐quarters reported changes in clinical practice. Scholars indicated improvements in knowledge and practice of HIV prevention, including pre‐exposure prophylaxis and managing medications and comorbidities. A third of the Scholars reported improvements in their clinical practices related to linking and retaining patients in HIV care, which demonstrated positive movement along the HIV care continuum, a key focus area of the National HIV AIDS Strategy.